Variants implicated in cortisone reductase deficiency do not contribute to susceptibility to common forms of polycystic ovary syndrome. - Draper, N; Powell, B; Franks, S; Conway, G; Stewart, P; McCarthy, M (2006)
OBJECTIVE: There are close phenotypic similarities between cortisone reductase deficiency (CRD), a rare abnormality of cortisone metabolism, and polycystic ovary syndrome (PCOS). As there is evidence that CRD results from digenic mutations involving the genes encoding 11beta-hydroxysteroid dehydrogenase type 1 (HSD11B1) and hexose-6-phosphate dehydrogenase (H6PD), we sought to establish whether CRD-associated variants in these genes, individually or in combination, influence susceptibility to PCOS. DESIGN: Case-control, family-based association and quantitative-trait analyses. PATIENTS: A UK case sample comprising 256 nuclear families ascertained from a PCOS offspring and 213 singleton PCOS cases plus 549 control subjects. MEASUREMENTS: All subjects were genotyped for CRD-related variants in HSD11B1 (rs12086634) and H6PD (rs6688832). Testosterone was measured with an in-house radioimmunoassay using ether extraction and dextran-coated charcoal separation. RESULTS: Case-control analyses revealed no differences in genotype distribution between PCOS and controls for rs12086634 or rs6688832 (both P = 0.84). Three per cent of cases and 2.4% of controls had genotype combinations (three or more variant alleles at the two sites) considered characteristic of CRD (P = 0.73). There were no departures from expectation in the family-based association studies, and no significant associations between genotypes (individually or in combination) and BMI, WHR or testosterone. CONCLUSIONS: The variants in HSD11B1 and H6PD typed, though implicated in causation of CRD, do not influence susceptibility to PCOS. It seems likely that additional variants within these genes are required for the development of CRD.